Produção de tomateiro cultivado com acrescent solus® - Schwertner, Diogo Vanderlei (2012)
The objectives of this study were: verify the adequation to the presuppositions of the mathematical model and, identify data transformation for productive and morphological variables of tomato in experiments in plastic tunnel and in field, considering each harvest date and grouped harvests during spring-summer and autumn-winter seasons; and, to evaluate the effect of the application of Acrescent Solus® in complementation and/or substitution to the mineral fertilization in coverage over productive and morphological variables, quality of fruit and color of leaves of tomato cultivated in plastic tunnel and in field during springsummer and autumn-winter seasons. Two experiments were conducted in plastic tunnel (spring-summer and autumn-winter) and one in field (spring-summer), both in a randomized block design with three replications in a bifactorial (2x4), with four additional controls. The tests of: non-additivity of Tukey, Lilliefors, Bartlett and Run Test, were used, respectively, for verify the adequation to the presuppositions of: additivity of the model, normality, homogeneity and randomness of errors. In cases of violation, the data were transformed and, submitted again to the analysis of the presuppositions of the mathematical model. The productive and morphological variables of tomato present adequation to the presupposition of additivity of the model. Violations of the productive and morphological variables occur to the presupposition of: normality, homogeneity and randomness of errors. The grouping of all harvests for analysis provides adequation of productive and morphological variables to the presuppositions of normality and homogeneity of errors. The data transformation that provides more proportion of adequation of productive and morphological variables to the presuppositions of normality, homogeneity and randomness of errors is the square root. In the spring-summer, the Acrescent Solus® does not alter the productive and morphological variables and, the quality of fruits of tomato, while, in the autumn-winter, it reduces the length, the width and the mass of fruits and, also, it does not alters the quality of fruits. The increase of the dose of Acrescent Solus®, combined with the mineral fertilization in coverage results in intensification of the green color of leaves, from the second and fourth harvest fruit in the spring-summer and autumn-winter, respectively, nevertheless, without showing favorable correlation with the expression of productive and morphological variables of tomato.